Analisis Makna Iman Kepada Allah Dalam Konteks Kekinian - Sumarta Sumarta (LPPM STAIS Dharma Indramayu, 2019)
This research aims to analyze the meaning of faith in God in the contemporary context. The presence of technology, social changes, and increasingly complex consumer culture has presented challenges and changes in how individuals understand and practice their religious beliefs. This study combines a multidisciplinary approach, using qualitative and quantitative research methods, including case studies, in-depth interviews, and surveys. The research findings show that the meaning of faith in God is a subjective phenomenon that varies among individuals and groups. Factors such as technology, social media, contemporary events, and cultural influences affect the meaning of faith and religious practices. These findings provide deep insights into how religious beliefs remain relevant in a changing society and can guide further research and studies in this field. Keywords: Religion, Contemporary context, Social and cultural changes